The evaluation of relation between vitamin B12 and body mass index - Atalay, Eray; Aslan, Nurullah; Şişman, Pınar (The European Research Journal, 2020)
Objectives: Obesity has become a pandemy all around the world, etiology of obesity consist multiple factors and it causes serious health problems. It is known that the low level of vitamin B12 has adverse effects on many systems, mainly cell DNA. In our study, it was planned to evaluate whether there is a relation between body mass index and serum vitamin B12 level. Methods: We included 168 patients aged 18-67 years, who did not have a chronic disease and who applied to the outpatient clinic in our center. We divided the patients into 3 groups according to the body mass index (BMI): Group I: normal weight (BMI: 18.50-24.99 kg/m2); Group II: overweight (BMI: 25-29.9 kg/m2) and Group III: obese (BMI: ≥ 30 kg/m2). Vitamin B12 levels were evaluated between these groups. Results: There was a statistically significant difference between the groups in terms of glucose, total cholesterol, HDL-cholesterol, LDL-cholesterol and triglyceride. Vitamin D levels were not statistically significant between the groups. The mean serum vitamin B12 levels of the individuals were 299 ± 125 pmol/L, 298 ± 148 pmol/L and 313 ± 143 pmol/L in Group I, Group II and Group III, respectively. There was no statistically significant difference and correlation between BMI and serum vitamin B12 levels in the groups. Conclusions: The etiology of obesity, a serious health problem in today’s society, has proven to be multifactorial. No significant association was found between BMI and vitamin B12 levels at the end of the study. It was concluded that similar studies should be performed with a large case series.